PEMERTAHANAN BAHASA BALI DALAM RANAH MEDIA SOSIAL INSTAGRAM - Made Reland Udayana Tangkas (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
The Balinese language as a major regional language should always be considered in terms of its resilience to face the dynamics of the times that tend to erode cultural elements. The Balinese language has also experienced marginalization due to the orientation of the people who tend to prioritize foreign culture as the influence of the uncontrolled tourism world. Thus, foreign languages are more in demand by modern society today than Balinese. Attention to this phenomenon was born from observers and activists of the Balinese language who feel that the Balinese language should be preserved and maintained as a mother tongue. These observers began to raise the Balinese language in the realm of social media "Instagram" as the most popular media, especially for teenagers. The preservation of the Balinese language as an idea that should be cultivated and studied continuously reflects the close relationship between language and social life. Moreover, social media as the latest communication trend dominates people's behavior patterns. An assessment of the preservation of the Balinese language in the realm of "Instagram" social media includes a discussion of the use of Balinese language forms and the social aspects underlying the use of the Balinese language. the forms of Balinese used can be distinguished between the Balinese Alus and Kepara languages both at the vocabulary and sentence levels. Then, the social aspects behind the use of the Balinese language as an effort to maintain it are cultural aspects, educational aspects, entertainment aspects, and social aspects.Keywords: Balinese language, Instagram, defense